2023
DOI: 10.1111/imj.16084
|View full text |Cite
|
Sign up to set email alerts
|

Intrapleural tissue plasminogen activator and deoxyribonuclease administered concurrently and once daily for complex parapneumonic pleural effusion and empyema

Abstract: BackgroundPleural infection is life‐threatening and increasingly prevalent. In addition to usual care, twice‐daily, separate administration of tissue plasminogen activator and deoxyribonuclease (tPA‐DNase) reduces radiological pleural opacity with lower surgical referral rates.AimsThis retrospective cohort study examines the use of once‐daily, concurrent administration of tPA‐DNase for complex parapneumonic pleural effusion and empyema.MethodsPatients with pleural infection who received intrapleural tPA‐DNase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
1
0
0
Order By: Relevance
“…The daily dosing of IET has been retrospectively studied with the results suggesting the safety and practicality of once-a-day dosing. However, the findings also suggested a higher surgical referral rate to what has been previously reported in the literature [ 56 , 57 ]. Furthermore, a study by Cheong et al revealed that a modified regimen of 16 mg of tPA and 5 mg of DNase can be safe and effective.…”
Section: Managementsupporting
confidence: 59%
“…The daily dosing of IET has been retrospectively studied with the results suggesting the safety and practicality of once-a-day dosing. However, the findings also suggested a higher surgical referral rate to what has been previously reported in the literature [ 56 , 57 ]. Furthermore, a study by Cheong et al revealed that a modified regimen of 16 mg of tPA and 5 mg of DNase can be safe and effective.…”
Section: Managementsupporting
confidence: 59%